(untitled) (المجلة العراقية للعلوم الاقتصادية, 2018)
The research aims to show the effects of pricing policy on products of animal by measuring and analyzing transactions nominal protection net for each item and see its effects addressed for the benefit of producers or consumers, and then measure the coefficient of nominal protection synthesis of all animal products studied (red meat, chicken, fish, milk and table eggs ), which is one of the major food commodities in the lives of citizens, have prodded the goods continues to rise in prices, especially in the siege, which could harm the consumption of these products. has been shown by the results of transaction protection nominal net calculated as less than one for all the goods studied in most years of the study (except for a few years), with the exception of red meat and that the values of transactions where the largest of any single-price policy that was established for producers of red meat and the interests of consumers for the rest of other commodities where producers bear an indirect tax. It was found that the high prices of goods for world prices which means that the price increase was the result of overlapping of some other policies Cablecast productivity and exchange rate policy because of the low value of the diner during the siege. The reference values of nominal protection coefficients on the synthesis of products of animal it is less than one during the years of siege and before any the interests of consumers (except for a few years), while after 2001 took more than one of any, the protection for producers of any state that because of the circumstances of the siege has supported the consumers and after 2001 and after the increase of incomes and improve the value of the currency had to be oriented towards supporting producers to increase production and provide animal products in the markets and reasonable prices to the consumer